I understand how 8 is arrived at. {empty set, {1},{2},{3},{2,3},{1,2},{1,3},{1,2,3}}

What I don't understand is why it how this relates to 2^3

Has it got something to do with the binomial theorem?

- Thread starter perusal
- Start date

I understand how 8 is arrived at. {empty set, {1},{2},{3},{2,3},{1,2},{1,3},{1,2,3}}

What I don't understand is why it how this relates to 2^3

Has it got something to do with the binomial theorem?

- Joined
- Jan 27, 2012

- Messages
- 5,042

It relates to the fact that 2^3 is **equal** to 8!

Yes, we can state:

\(\displaystyle P_n=\sum_{k=0}^n\left({n \choose k}\right)=\sum_{k=0}^n\left({n \choose k}1^{n-k}\cdot1^{k}\right)=(1+1)^n=2^n\)

Thanks for your help.

How do we get from

\(\displaystyle \sum_{k=0}^n\left({n \choose k}1^{n-k}\cdot1^{k}\right)\)

to

\(\displaystyle (1+1)^n\)

- Joined
- Nov 24, 2012

- Messages
- 1,815

Via the binomial theorem.Thanks for your help.

How do we get from

\(\displaystyle \sum_{k=0}^n\left({n \choose k}1^{n-k}\cdot1^{k}\right)\)

to

\(\displaystyle (1+1)^n\)

- Joined
- Nov 12, 2017

- Messages
- 4,110

Think about how you expand (a + b)^n by the binomial theorem. Then replace a and b with 1.

- Joined
- Jan 29, 2005

- Messages
- 8,319

You need to know the basic binomial expansion formula:How do we get from \(\displaystyle \sum_{k=0}^n\left({n \choose k}1^{n-k}\cdot1^{k}\right)\)

to \(\displaystyle (1+1)^n\)

\(\displaystyle {(x + y)^n} = \sum\limits_{k = 0}^n {\binom{n}{k}{x^{n - k}}{y^k}} = {x^n} + n{x^{n - 1}}y + \cdots nx{y^{n - 1}} + {y^n}\)

Now if \(\displaystyle x=1~\&~y=1\) we have \(\displaystyle (1+1)^n=2^n\)

Thus \(\displaystyle {(2)^n} = \sum\limits_{k = 0}^n {\binom{n}{k}}\)

All you need to know now \(\displaystyle \binom{n}{k}=\frac{n!}{k!(n-k)!}\) from \(\displaystyle n\) choose \(\displaystyle k\), a subset of size \(\displaystyle k\) in a set of size \(\displaystyle n\).